PENATAAN SISTEM DRAINASE PERMUKIMAN BERBASIS MASYARAKAT DENGAN METODE PERENCANAAN PARTISIPATIF DI KELURAHAN PONCOL KECAMATAN PEKALONGAN TIMUR - Dwi Kumalasari; Tisnawati Tisnawati (LPPM Universitas Pekalongan, 2018)
is the case of puddle that occurred in Kelurahan Poncol Kecamatan Pekalongan Timur which resulted from damage to the drainage or less optimal drainage performance. Drainage damage is often caused by the community around the settlement. The low sense of ownership and responsibility for maintaining drainage is what causes drainage to not function optimally. Therefore, structuring the settlement drainage system using participatory methods aimed at increasing community participation and involvement in handling puddle problems, so that the drainage system built can be sustainable and foster a sense of community ownership of existing drainage. Based on the results of this method, planning by involving students functions more optimally than planning that does not involve the community. This is because the community is more aware of the location of the arrangement of the drainage system that will be planned.